Waiting for the next crash: The Minskyan lessons we failed to learn - L. Randall Wray (Levy Economics Institute of Bard College, 2011)
Senior Scholar L. Randall Wray lays out the numerous and critical ways in which we have failed to learn from the latest global financial crisis, and identifies the underlying trends and structural vulnerabilities that make it likely a new crisis is right around the corner. Wray also suggests some policy changes that would shore up the financial system while reinvigorating the real economy, including the clear separation of commercial and investment banking, and a universal job guarantee.
Keywords: 330